Designing a Safe and Friendly Environment for Women and Children in Rural Community - Chawa, Anif Fatma; Moch Hisyam Putra; Arawindha, Ucca; Puspita Rahayu, Dewi (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2024)
The need to build a safe and friendly environment has developed to respond to the increasing number of vulnerable issues which have been faced by children and women. Nevertheless, strategies to build a safe and friendly environment in rural areas are rarely discussed. This study outlined the macro perspective which considers structural and cultural change as a strategy to design a positive environment for women and children in the village. This perspective is adopted due to the fact that the places where women and children live, either in city or rural areas could become the factors causing women and children to live in a vulnerable environment. This design consists of two aspects which are the building of an institutional network and program recommendations. The implementation of an institutional network requires three principles or strategies which are participation, integration between women and children development programs, and involve various parties or community organizations including village government, professionals, scholars, as well as formal dan informal groups which are formed by rural community members, as facilitators and volunteers in the development programs. All these principles should be adopted to undertake program recommendations to meet the rights of children in health, education, legal advice, security, and peace.